The Relevance of Islamic Educational Characteristics In The 21st-Century: (a Study on Al-Suhrawardi's Thoughts in Adabul Muridin Book) - Muhamad Arif; Mohd Kasturi Nor bin Abd Aziz (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
This research is a novelty study, which discusses critical analysis, with a focus on the relevance of character education for students in 21st-century educational institutions from the perspective of As-Suhrawardiy in his book Adabul Muridin. The focus of the research is on how the model of moral education from the perspective of Sufism (a study of As-Suhrawardiy's thoughts) and how the relevance of As-Suhrawardiy's perspective of moral education in the 21st century. This study uses a literature review approach from As-Suhrawardiy's book Adabul Pupils. Analysis of research data, using analysis content as Elo et al and Marsh phases from data collection, coding, and reporting of the results. The results show that As-Suhrawardiy in his book Adabul Muridin explicitly states the importance of inculcating morals in the world of education, especially in the 21st century with the massive development of information technology. At the stage of As-Suhrawardiy's educational concept in explaining the concept of akhlaqi tasawwuf, there are three stages in strengthening moral education; takhalli (the process of cleansing the human self from bad deeds), tahalli (the process of filling from individuals by getting used to noble character in every action), and tajalli (the process of muroqabah (feeling the presence of Allah) on the individual with his god). A concept that is quite relevant to the challenges in the 21st century involves strengthening character education and strengthening the 4C competencies of each individual. Â